2010
DOI: 10.1099/jmm.0.013110-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma salivarium detected in a microbial community with Candida glabrata in the biofilm of an occluded biliary stent

Abstract: Mycoplasma salivarium, preferentially an inhabitant of the human oral cavity, has rarely been found in other locations associated with disease. We describe here, for what is believed to be the first time, the detection of M. salivarium, together with Candida glabrata, in an occluded biliary stent of an icteric, cholestatic patient. Case reportA 71-year-old man with known alcoholic liver cirrhosis was admitted with painless jaundice, an increase in abdominal circumference, dark urine and acholic faeces of 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…A number of research works have demonstrated that a variety of medical devices (including intravenous and arterial lines, urinary catheters, cardiac and biliary stents), can harbor biofilms that infect them, resulting in the need for device replacement [12,16]. The present results show the ability of Mycoplasma to adhere to nitinol surfaces.…”
Section: Effect Of Human Serum On Biofilm Formation By Oral Mycoplasmsupporting
confidence: 49%
See 1 more Smart Citation
“…A number of research works have demonstrated that a variety of medical devices (including intravenous and arterial lines, urinary catheters, cardiac and biliary stents), can harbor biofilms that infect them, resulting in the need for device replacement [12,16]. The present results show the ability of Mycoplasma to adhere to nitinol surfaces.…”
Section: Effect Of Human Serum On Biofilm Formation By Oral Mycoplasmsupporting
confidence: 49%
“…In a recent study, Henrich et al [12] reported the finding of two inhabitants of the oral cavity in a biliary stent of a cholestatic patient: Mycoplasma salivarium, and Candida glabrata.…”
Section: Introductionmentioning
confidence: 99%
“…Incidental findings identified M. salivarium as causative agent of disseminated infections, such as a chronic joint infection in a patient with hypogammaglobulinaemia [32]. M. salivarium was found in brain abscesses of two patients [33], in an occluded biliary stent in polymicrobial community with Candida glabrata [34] and as causative agent of a pleural empyema [35].…”
Section: Discussionmentioning
confidence: 99%
“…In house TaqMan PCRs for the quantification of Mycoplasma salivarium ( M. salivarium ) [12], Veillonella parvula ( V. parvula ) [13], S. aureus [14], P. gingivalis [15], Parvimonas micra ( P. micra ) [16], and T. forsythia [15] (Table 1) were carried out in a total volume of 25 μl consisting of 1× Eurogentec qPCR MasterMix (Eurogentec, Seraing, Belgium) without ROX (containing buffer, dNTPs (including dUTP), HotGoldStar DNA polymerase, 5 mM MgCl 2 , uracil-N-glycosylase and stabilizers (RT-QP2X-03NR, Eurogentec)), 300 nM each forward and reverse primer, 200 nM labeled probe, and 2.5 μl of template DNA (primer and probes are listed in Tables 1 and 2). Amplicon carrying plasmids were used in concentrations of 10 5 and 10 2 copies/μl as quantification standards.…”
Section: Methodsmentioning
confidence: 99%